2010
DOI: 10.1097/pas.0b013e3181c76a49
|View full text |Cite
|
Sign up to set email alerts
|

The Basaloid Cell is the Best Tissue Marker for Human Papillomavirus in Invasive Penile Squamous Cell Carcinoma: A Study of 202 Cases From Paraguay

Abstract: Human papillomavirus (HPV) has been reported in 12-82% of penile squamous cell carcinomas (SCC). There is an association of the virus with basaloid and warty carcinomas but the reported prevalence is variable. The causes of these variations are not clear. They may be owing to geographic differences, the use of different techniques to detect HPV, the status of the original paraffin blocks, or to variable criteria in tumor classification. The aims of the study were to determine the prevalence of HPV in penile SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
72
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 45 publications
8
72
2
Order By: Relevance
“…Our studied showed that the only positive association was between the prevalence of HPVhigh in 75% of basaloid tumors, with worse prognosis. Cubilla et al (20) reported the same association.…”
Section: Discussionsupporting
confidence: 64%
“…Our studied showed that the only positive association was between the prevalence of HPVhigh in 75% of basaloid tumors, with worse prognosis. Cubilla et al (20) reported the same association.…”
Section: Discussionsupporting
confidence: 64%
“…They were among those more commonly associated with the virus. 13 However, there is no adequate clinical, pathological, and outcome characterization of wartybasaloid carcinomas. In this report, we are presenting a large number of cases to describe these features.…”
mentioning
confidence: 99%
“…The association of these special subtypes of penile carcinomas, both showing different morphological features and biological behavior, [2][3][4]7 is not surprising considering their presumed common human papillomavirus-related pathogenesis. [11][12][13] In a recent large survey of human papillomavirus in invasive penile tumors, warty-basaloid carcinomas were recognized as a special tumor subtype. They were among those more commonly associated with the virus.…”
mentioning
confidence: 99%
“…Reported HPV rates also vary widely for invasive urothelial carcinomas, ranging from 0 to 100%. [38][39][40] This variation may be due to the different methods of detection used in the studies. For frozen or fresh tissue, PCR is considered to be the gold standard, 41 although PCR technique is frequently blamed for being oversensitive, subject to contamination, and false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Basaloid and warty morphologies are characteristic of HPV-associated squamous cell carcinomas and have been shown to correlate with viral status in oropharyngeal, 8 vulvar, 5 penile, 38 and anal carcinomas. 53 Bladder squamous cell carcinoma very rarely shows basaloid/warty features, which is consistent with the infrequent finding of HPV in bladder squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%